Types and Social Functions of English Slang in Urban and Rural Youtube Vlogs - Siti Kholilah; Ruminda Ruminda; Erfan Muhammad Fauzi (Journal of English Language and Education, 2026)
Language functions as a dynamic social practice through which individuals construct identities, negotiate relationships, and express group membership, with slang representing one of its most flexible linguistic forms. Although previous studies have extensively examined slang in written digital communication, comparative analyses of spoken slang used by urban and rural content creators remain limited. This study aims to investigate the types, distribution patterns, and social functions of English slang in urban and rural YouTube vlogs. A qualitative comparative approach was employed by analysing transcriptions from eight unscripted YouTube vlog videos produced by four American content creators. The data were examined using Allan and Burridge’s (2006) classification of slang and Eble’s (1996) functional framework. The findings demonstrate a clear distinction between the two groups. Urban creators predominantly employ word reduction, including clipping and acronyms, together with fresh and creative slang expressions. In contrast, rural creators rely primarily on semantic innovation through fresh and creative expressions. Functionally, urban creators use slang to project identity and signal subcultural affiliation, whereas rural creators emphasize sociability and reduced formality to foster interpersonal closeness. These findings suggest that geographical and cultural backgrounds may influence informal language practices across contemporary digital media.